bicoid and the terminal system activate tailless expression in the early Drosophila embryo. - Pignoni, F.; Steingrimsson, E.; Lengyel, J.A. (Development, 1992)
In the early Drosophila embryo, the maternal terminal genes are required for formation of the acron at the anterior and the telson at the posterior. We show here that the terminal system, a signal transduction pathway active at the poles of the embryo, is required to activate transcription of the key zygotic gene tailless (tll) in two symmetrical domains. Consistent with the characterization of the tll protein as a putative transcription factor (a member of the steroid receptor superfamily) that represses segmentation genes and activates terminal-specific genes, we observe a correlation between the presence of the posterior cap of tll expression and differentiation of a telson. While the maternal patterning systems of the Drosophila embryo function for the most part independently, the maternal anterior system, in which the bicoid (bcd) protein functions as a graded morphogen, is required together with the terminal system to establish the acron. This dual requirement is evident at the molecular level in the control of tll expression. We find that bcd and the terminal system are required together to activate the anterior-dorsal stripe of tll expression that is correlated with formation of the acron. In the absence of bcd, the anterior cap of tll expression established by the terminal system persists and an ectopic telson forms at the anterior, while in the absence of terminal system activity only an abnormal anterior stripe forms. This is the first described example of how, by jointly controlling expression of the same gene, two systems of positional information function together to set unique positional values.